2022
DOI: 10.3390/su14042013
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Different Envelope Configurations via Optimization Analysis and Thermal Performance Indicators: A Case Study in a Tropical Climate

Abstract: Passive solutions for more energy-efficient buildings are critical to improving our odds in the current energy crisis. This work focuses on assessing the thermal performance of different envelope construction layouts in a tropical climate through proposed indicators regarding the thermal mass degree (TMD) and insulation degree (ID). For this, a numerical study was performed for a reference building (RB) in Panama City and validated with the electricity consumption bills. Behavioral and sensitivity analyses wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 21 publications
0
6
0
1
Order By: Relevance
“…The variables of interest selected for this study were electricity consumption by cooling (air conditioning) and hours of non-comfort with 80% acceptability (ASHRAE 55) [32]. Both temperature options and air conditioning usage schedules were selected based on survey results, while building materials were selected based on local market layout [33]. The design variables with the selected options to be evaluated are shown in Table 3.…”
Section: Thermo-energy Evaluation By Parametric Analysismentioning
confidence: 99%
“…The variables of interest selected for this study were electricity consumption by cooling (air conditioning) and hours of non-comfort with 80% acceptability (ASHRAE 55) [32]. Both temperature options and air conditioning usage schedules were selected based on survey results, while building materials were selected based on local market layout [33]. The design variables with the selected options to be evaluated are shown in Table 3.…”
Section: Thermo-energy Evaluation By Parametric Analysismentioning
confidence: 99%
“…This is the reason why one of the activities planned within the IDDS22-30 research project is aimed precisely at a mapping of existing buildings, particularly with reference to the research area identified in Panama City. Constructive features have been considered in studies such as [20] and [21]. However, with reference to the definition of zero-energy buildings concerning new constructions.…”
Section: Description Of the Buildings Stockmentioning
confidence: 99%
“…Windows, walls, and roofs are the areas most prone to have heat transfer with the environment. A significant amount of energy in the form of heat enters a space through the roof, as it is the part where the most energy is concentrated by radiation and convection due to continuous solar exposure during the day [ 1 , 2 ]. Critical heat gains through the roof were obtained when performing yearly monthly averaged simulation in Panama’s climate conditions (between 780 and 900 kWh) [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…A significant amount of energy in the form of heat enters a space through the roof, as it is the part where the most energy is concentrated by radiation and convection due to continuous solar exposure during the day [ 1 , 2 ]. Critical heat gains through the roof were obtained when performing yearly monthly averaged simulation in Panama’s climate conditions (between 780 and 900 kWh) [ 1 ]. Therefore, it is important to conduct a study that allows for proposing solutions related to this issue.…”
Section: Introductionmentioning
confidence: 99%